2015
DOI: 10.1002/2015wr017318
|View full text |Cite
|
Sign up to set email alerts
|

Predicting colloid transport through saturated porous media: A critical review

Abstract: Understanding and predicting colloid transport and retention in water‐saturated porous media is important for the protection of human and ecological health. Early applications of colloid transport research before the 1990s included the removal of pathogens in granular drinking water filters. Since then, interest has expanded significantly to include such areas as source zone protection of drinking water systems and injection of nanometals for contaminated site remediation. This review summarizes predictive too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
195
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 237 publications
(208 citation statements)
references
References 305 publications
(727 reference statements)
5
195
0
Order By: Relevance
“…Despite the difficulty in simulation, high-frequency flow and moisture dynamics forced by wave swash are important for understanding aspects of beach aquifer systems such as subsurface geochemical conditions, particulate transport, chemical fate, surface evaporation dynamics, and aeolian sediment transport (Geng et al, 2015(Geng et al, , 2016bHuettel et al, 1996;Kim et al, 2017;Malott et al, 2017;Molnar et al, 2015;Nickling & Davidson-Arnott, 1990;Wu et al, 2017). Wave swash strongly controls the flux of water into beach aquifers, as well as flow paths, residence times, and mixing of various chemical species beneath the swash zone (Geng et al, 2014;Malott et al, 2016;Robinson et al, 2014;Xin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the difficulty in simulation, high-frequency flow and moisture dynamics forced by wave swash are important for understanding aspects of beach aquifer systems such as subsurface geochemical conditions, particulate transport, chemical fate, surface evaporation dynamics, and aeolian sediment transport (Geng et al, 2015(Geng et al, , 2016bHuettel et al, 1996;Kim et al, 2017;Malott et al, 2017;Molnar et al, 2015;Nickling & Davidson-Arnott, 1990;Wu et al, 2017). Wave swash strongly controls the flux of water into beach aquifers, as well as flow paths, residence times, and mixing of various chemical species beneath the swash zone (Geng et al, 2014;Malott et al, 2016;Robinson et al, 2014;Xin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The functional groups cause charge properties locally different from those of bulk biochar surfaces. Various studies (Bradford and Torkzaban, 2013; Johnson et al, 1996; Li et al, 2017; Molnar et al, 2015; Pazmino et al, 2014; Shen et al, 2013) have shown that the presence of surface charge heterogeneity can increase colloid deposition in primary minima by locally reducing the repulsive energy barrier and increasing primary minimum depths and thereby increasing the adhesive forces. Furthermore, the scanning electron microscopy image in Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Understanding the mechanisms associated with these phenomena can improve risk assessment after a contaminant spill or subsurface pathogen outbreak. Recently published review articles covering both saturated (Molnar et al ., 2015) and unsaturated (Flury & Aramrak, 2017) colloid transport describe modelling and experimental efforts aimed at more accurate prediction of the fate of colloids in the environment. However, these models and calculations are constructed under highly idealized conditions, therefore additional experimental evidence will be required for further model validation and verification.…”
Section: Introductionmentioning
confidence: 99%